Exploring Idiomatic Expressions in Demi Lovato's 'Heart Attack': A Student Translation - Aminah Qurrata Aini Matoka; Novriyanto Napu; Sri Widyarti Ali (Transbahasa, 2024)
This study aims to determine the accuracy of students' translations of idiomatic expressions in song lyrics. The Data was collected from 24 students in the 4th semester of the English Department at Gorontalo State University. The song lyrics used for the study were from